Quality of cord blood cryopreserved for up to 5 years - Lee, Hye Ryun (Korean Society of Hematology; Korean Society of Blood and Marrow Transplantation; Korean Society of Pediatric Hematology-Oncology; Korean Society on Thrombosis and Hemostasis, 2014)
BACKGROUND: Although cord blood (CB) is a well-known source of hematopoietic stem cells, uncertainties exist regarding the quality of cryopreserved CB. We investigated the changes in quality of CB units according to the duration of cryopreservation. METHODS: We analyzed CB units that were rejected from the Seoul Metropolitan Government Public Cord Blood Bank inventory after conventional processing, because of unsuitability for allogeneic transplantation. Two hundred CB units that were cryopreserved from 1 year to 5 years were selected. After thawing the cryopreserved CB units, the total nucleated cell (TNC) count, CD34+ cell count, number of colony-forming units (CFU), aldehyde dehydrogenase (ALDH) level, cell viability, and apoptosis were analyzed. We conducted a comparative analysis to identify the presence of statistically significant differences in the recovery rates of the TNC and CD34+ cell counts and to compare the results of ALDH level, the cell viability test, the apoptosis test, and CFU analysis among groups according to the duration of cryopreservation. RESULTS: The recovery rates of the TNC count, the CD34+ cell count, and cell viability did not differ significantly according to the duration of cryopreservation. ALDH analysis, the cell viability test, and the apoptosis test did not reveal any increasing or decreasing trend according to the duration of cryopreservation. Further, the numbers of CFU-granulocyte/macrophage and CFU-granulocyte/erythrocyte/macrophage/megakaryocyte did not differ significantly according to the duration of cryopreservation. CONCLUSION: These results suggest that the quality of CB is not affected by cryopreservation for up to a period of 5 years.